FAKTOR PEMENGARUH PERILAKU SISWA DAN MAHASISWA MENYONTEK - Christine Masada; Sabrina Dachmiati (Sosio e-Kons, 2016)
This research aims to know the tendency of cheating, the dominant indicator which causes the behavior of cheating, the effective factor of cheating, the category of dominant background which supports the behavior of cheating and the effect of cheating among pupils and students. The research used several methodologies such as case study, survey, experiment in which the research examines the hypothesis stating the correlation between independent variable and dependent variable. Then, the survey was developed based on research of explanatory and confirmatory. The data was collected by conducting interview, observation and questionnaire. The experiment method was also used to implement the main instrument techniques and the sub-main in the way of learning, self-motivating, technique of material mastery, self-developing and self-understanding as well as self-reconstructing. The result of research showed that the effective factor of students’ cheating behavior tendency was very strong. Based on the data, the behavior of cheating can happen because of the opportunity and availability. It was promoted by the wrong self-conception regardless of religion ,environment and role model. In other words, the closed role models were very effective to determine the choice of behavior.Keywords: Attitude, student, student university, cheat.